2013
DOI: 10.1186/1475-2875-12-296
|View full text |Cite
|
Sign up to set email alerts
|

Anti-erythropoietin antibody levels and its association with anaemia in different strains of semi-immune mice infected with Plasmodium berghei ANKA

Abstract: BackgroundMalaria anaemia is still a major public health problem and its pathogenesis still unclear. Interestingly, the progression of anaemia is at relatively low parasitaemia with some mortality in the semi-immune individuals in the endemic areas despite adequate erythropoietin (EPO) synthesis. A recent study has shown that treatment with exogenous anti-erythropoietin (anti-EPO) antibodies (Ab) of infected mice gives protection against malaria infection, suggesting an important role for anti-EPO Ab in malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…Mechanisms proposed to be involved in the anaemia in malaria have ranged from rupture of infected red blood cell (iRBC) due to parasite proliferation [ 19 ], immune mediated dependent destruction of RBC (antibody, complement, cytokines, cellular) [ 20 24 ] to suppression of the bone marrow [ 25 ]. A study has shown variation of IL-17 levels in different semi-immune mice strains implicating a role of IL-17 in RBC loss due to Plasmodium infection [ 24 ]. Recent reports have also shown IL-17 relationship with SMA [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms proposed to be involved in the anaemia in malaria have ranged from rupture of infected red blood cell (iRBC) due to parasite proliferation [ 19 ], immune mediated dependent destruction of RBC (antibody, complement, cytokines, cellular) [ 20 24 ] to suppression of the bone marrow [ 25 ]. A study has shown variation of IL-17 levels in different semi-immune mice strains implicating a role of IL-17 in RBC loss due to Plasmodium infection [ 24 ]. Recent reports have also shown IL-17 relationship with SMA [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these studies linking IL-17 with haemoglobin (Hb) loss, other studies have shown IL-17 to be involved in multiple organ dysfunction [ 28 ], and also found to be associated with higher risk in developing cerebral malaria (CM) [ 29 ]. Since previous studies have reported the recovery of a group of semi-immune mice at low parasitaemia [ 23 , 24 ], and also for the fact that IL-17 was implicated in one study [ 24 ], it is hypothesized that IL-17 is involved in the recovery/protection of the semi-immune mice at low Hb levels. The aim of this study, therefore, was to assess levels of IL-17 in anaemic condition as well as evaluate its association with host genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, no association was found between hepcidin and Hb levels and low hepcidin levels are found in SMA patients (Howard et al 2007;de Mast et al 2010;Burte et al 2013;Glinz et al 2015). Anti-Epo auto-Abs are negatively correlated with Hb levels in semi-immune mice, which could point to an additional mechanism why erythroid progenitors are not responding accurately (Helegbe et al 2013). Also phagocytosis of erythroid precursors and dyserythropoiesis, i.e.…”
Section: Erythrocyte Destruction and Ineffective Erythropoiesismentioning
confidence: 75%
“…Others' studies have also found that anti-EPO antibody prevalence in ESRD patients who receive ESA may be associated with EPO resistance and demand, resulting in anemia (9,20). Studies in patients with some autoimmune diseases and patients with HIV revealed high levels of anti-EPO antibodies (8,21). Thus, EPO antibodies may participate in a variety of diseases.…”
Section: Discussionmentioning
confidence: 98%
“…In recent decades, the anti-EPO antibody and anti-EPO receptor (anti-EPOR) antibody have been reported to be associated with EPO resistance (8)(9)(10). In addition, they may play an important role in anemia among maintenance dialysis patients combined with insufficient EPO production (6,11).…”
Section: Introductionmentioning
confidence: 99%